THE HEROIC BATTLE OF MUSA DAGH ACCORDING TO THE TESTIMONIES OF THE EYEWITNESS-PARTICIPANTS AND THE COMMANDMENT OF FRANZ WERFEL - Svazlian, Verjine (Armenian Folia Anglistika, 2025)
As a part of the Armenian nation, the Musa Dagh people, in particular, have felt the necessity of regeneration of the national statehood, its meaning and value, particularly following the fall of the 300-year-old flourishing statehood of Cilicia and during the 600 years of absence of power. The Musa Dagh people, who were forged and had gained sagacity in the heroic battles for survival, have formulated their feat very concisely: “Freedom is on the tip of the rifle,” (Svazlian 2015, p. 207) that is to say, freedom can be obtained only by the force of arms, which is followed by “Freedom is on the tip of the flag,” (Svazlian 2015, p. 207) that is to say, statehood is the guarantee of freedom.